Silicon Application Improves Lodging Resistance and Grain Yield of Traditional Rice Genotypes in the Coastal Ecosystem of Bangladesh (SAARC Journal of Agriculture, 2026)
Lodging is a major constraint to rice farming in the coastal ecosystem of Bangladesh, particularly among traditional tall genotypes that are otherwise well-adapted to local stress conditions. This study was aimed to evaluate the effects of silicon (Si) supplementation on lodging resistance, growth, and yield performance of ten traditional rice genotypes under pot culture conditions. Two levels of silicon (0 and 100 mg Si kg⁻¹ soil) were tested in a factorial randomized design. Results revealed that Si application significantly reduced lodging percentage (from 21.4% to 15.4%) and enhanced grain yield (from 12.1 g to 13.7 g pot⁻¹) and straw yield (from 30.8 g to 34.0 g pot⁻¹). Significant genotypic variation was observed for all measured parameters. Sakkorkhana and Kalojira showed the highest increases in grains panicle-1 (142.6% and 51.2%, respectively) under Si treatment. Moulata and Sadamota achieved the highest biomass and yield, while Dudhkalom exhibited strong lodging resistance. Silicon uptake and content in both grain and straw increased significantly with Si application and correlated positively with yield components. These findings suggest that silicon application enhances lodging resistance and yield in traditional rice genotypes, with varied responses among genotypes. Integration of silicon fertilization with genotype selection could be an effective strategy for improving rice production in coastal Bangladesh.SAARC J. Agric., 23(2): 93-109 (2025)